Wartość stylistyczna wybranej leksyki w felietonach Krzysztofa Stanowskiego = Stylistic value of the selected lexis in Krzysztof Stanowski`s columns - Gorzelana, Joanna; Warchoł, Karol (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the lexis present in sports columns by Krzysztof Stanowski, a popular journalist in Poland. The author brings his language closer to the colloquial Polish by introducing phraseologisms and colloquial vocabulary (e.g. "facet"). He also uses borrowings (e.g. "fairplay") and neologisms (e.g. "wykartkować"), which makes his texts more attractive.
Keywords: Stanowski, Krzysztof (1982- ); felieton; leksyka; piłka nożna; column; lexis; football